Aspects of Human Capital Management and Employee Job Performance: The Moderation Role of Perceived Organizational Support - Abel Gebremedhn; Work Mekonnen; Wubshet Bekalu Mulusew (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This study examines the aspects of human capital management and its effects on employee job performance and the moderation role of perceived organizational support. Design/Methods/Approach: This study is structured on a quantitative approach, with stratified and simple random sampling techniques. This study reports the responses of 426 respondents from twelve banking institutions in Addis Ababa, Ethiopia. Exploratory and confirmatory factor analyses were applied to test the factors and verify the factor structure of a set of observed variables. The scales were tested for reliability and validity. Structural equation modeling with AMOS was used to test the hypothesized relationships. Findings: The results show that the aspects of human capital management, namely knowledge accessibility, learning capacity, workforce optimization, leadership practice, and career advancement, are positively related to employee job performance. Moreover, the results also reveal that perceived organizational support positively moderates the relationship between knowledge accessibility, learning capacity, leadership practice, career advancement, and employee job performance. Conversely, it is shown that perceived organizational support has an insignificant moderation effect on the relationship between workforce optimization and employee job performance Originality: Our research highlights the importance of focusing on the intangible assets of an organization (i.e., human capital). Besides, this study contributes to creating a new theoretical framework for the relationship between the aspects of HCM, perceived organizational support, and employee job performance by integrating crucial factors that have not been previously connected.